STUDENTS’ SATISFACTION ON ENGLSH LEARNING DURING COVID-19 PANDEMIC AT SMP N 1 WONGSOREJO - Arin Inayah; Abdul Halim; Mega Ayu Mayangsari (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2023)
This research aimed to know the satisfaction of the third grade students in English online learning during pandemic at SMPN 1 Wongsorejo. The scope of this study is to analyze the students satisfaction in learning English. The limitation of this study is students satisfaction in learning English during covid-19 pandemic of the third grade students at SMPN 1 Wongsorejo. The indicators of the research are tangible, reliability, responsiveness, assurance and empathy. This study used quantitative research. The subjects of the research are the 30 students of the third “C” grade at SMPN 1 Wongsorejo. The instruments used to collect the data is an questionnaire. The researcher made questionnaire in the form of positive statements for each stage and there were 25 statements (5 statements in tangible (facilities), 5 statements in reliability, 5 statements in responsiveness (willingness to help), 5 statements in assurance (ability to convey trust and confidence), and 5 statements in empathy). The students’ satisfaction would be calculated based on descriptive data analysis percentages and benchmarks. The finding of the research showed the satisfaction of the third grade students in English online learning during pandemic at SMPN 1 Wongsorejo is categorized as very high satisfaction with satisfaction score 86,27%.